(untitled) (Editora Impacto Científico, 2025)
Family farming plays a fundamental role in food production in many regions of the world, contributing to food security, job creation and economic development in rural areas. This end-of-course work seeks to conceptualize family farming, its production practices and its relationship with organic production. By means of a bibliographic review, a systematic process of searching for, collecting and analyzing information and knowledge available in academic and scientific publications, books, articles, theses, dissertations and other relevant bibliographic sources on a given topic, the aim was to highlight the contributions of family farming to the conservation of biodiversity, the preservation of traditional practices, the maintenance of local culture and the provision of healthy, quality food for the population. The analysis of the results points to the need to strengthen and support family farming and organic production as strategies for promoting sustainable development, reducing social inequalities and guaranteeing the population’s food sovereignty.